Aesthetics and Spatiality. Garroni, Kant and Cassirer - Morawski, Tommaso (Aesthetica Preprint, 2022)
In this essay, I would like to discuss a topic inherent to Emilio Garroni’s philosophical production that has sometimes been overlooked by his interpreters yet could still offer a valid orientation to those scholars who, for various reasons, deal with spatial thought and its multiple ramifications. I am referring to the connection between the set of meta-theoretical problems that arise in relation to the notion of spatiality and aesthetics, understood according to Garroni’s well-known definition as a “non-special philosophy”. The general idea of the essay is to examine the considerations Garroni dedicated to the paradox of spatiality and then trace, also through a comparison with the work of Kant and Cassirer, a possible line of development of Garroni’s thought in a “geo-aesthetic” perspective, that is, in resonance with that research project that aims to “recover the full meaning of the Greek term aisthesis from a geographical point of view”.